Physics of Biological Membranes (Springer International Publishing, 2018)
This book mainly focuses on key aspects of biomembranes that have emerged over the past 15 years. It covers static and dynamic descriptions, as well as modeling for membrane organization and shape at the local and global (at the cell level) scale. It also discusses several new developments in non-equilibrium aspects that have not yet been covered elsewhere. Biological membranes are the seat of interactions between cells and the rest of the world, and internally, they are at the core of complex dynamic reorganizations and chemical reactions. Despite the long tradition of membrane research in biophysics, the physics of cell membranes as well as of biomimetic or synthetic membranes is a rapidly developing field. Though successful books have already been published on this topic over the past decades, none include the most recent advances. Additionally, in this domain, the traditional distinction between biological and physical approaches tends to blur. This book gathers the most recent advances in this area, and will benefit biologists and physicists alike. .